Cost Utility Analysis of Dupilumab Versus Endoscopic Sinus Surgery for Chronic Rhinosinusitis With Nasal Polyps. (3rd April 2020) - Scangas, George A.; Wu, Arthur W.; Ting, Jonathan Y.; Metson, Ralph; Walgama, Evan; Shrime, Mark G.; Higgins, Thomas S.
Abstract : Objective: Both endoscopic sinus surgery (ESS) and biologic therapies have shown effectiveness for medically‐refractory chronic rhinosinusitis with nasal polyps (CRSwNP) without severe asthma. The objective was to evaluate cost‐effectiveness of dupilumab versus ESS for patients with CRSwNP. Study Design: Cohort‐style Markov decision‐tree economic model with a 36‐year time horizon. Methods: A cohort of 197 CRSwNP patients who underwent ESS were compared with a matched cohort of 293 CRSwNP patients from the SINUS‐24 and SINUS‐52 Phase 3 studies who underwent treatment with dupilumab 300 mg every 2 weeks. Utility scores were calculated from the SNOT‐22 instrument in both cohorts. Decision‐tree analysis and a 10‐state Markov model utilized published event probabilities and primary data to calculate long‐term costs and utility. The primary outcome measure was incremental cost per quality‐adjusted life year (QALY), which is expressed as an Incremental Cost Effectiveness Ratio. One‐way and probabilistic sensitivity analyses were performed. Results: The ESS strategy cost 50, 436.99 and produced 9.80 QALYs. The dupilumab treatment strategy cost 536, 420.22 and produced 8.95 QALYs. Because dupilumab treatment was more costly and less effective than the ESS strategy, it is dominated by ESS in the base case. One‐way sensitivity analyses showed ESS to be cost‐effective versus dupilumab regardless of the frequency of revision surgery and at any yearly cost of dupilumab above 855. Conclusions: The ESS treatment strategy is more cost effective than dupilumab for upfront treatment of CRSwNP. More studies are needed to isolate potential phenotypes or endotypes that will benefit most from dupilumab in a cost‐effective manner. Level of Evidence: 2C Laryngoscope, 131:E26–E33, 2021